(3GdeNJGQ ef OjhGf eOjM GdfHi Udi Gddg Ydjg hSdes - (3jMji Hf jhSa Hf jMji Hf efUhQ Hf GdeYeQ Hf YHO GdYRjR GdUQUQj, LeGd GdOjf CHh eMeO,J (B656 (3g` s ((3Ydi Hf YeQ Hf Ydi GdTGaYi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI GdbOhI eGOM QShd Gddg Udi Gddg Ydjg hSde LeGd GdOjf CHh RcQjG jMji Hf jhSa Ydi bGajI GdgeRI SHMGf ef ddhQi ai CQVg PQG hCMSf GdUfY HGdEJbGf s
(3BNQgG (B:s
(3Ydjc ef Gdegjef cd hbJ SdGe dG jMGhd Yfc fCjkG hdG RGdJ dc GdCfhGQ JgOi hai GdCNQi dc GdRdai JgjC Je GdeNJGQ ef eOjM QShd Gddg Udi Gddg Ydjg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs